Study on Development and Validation of Stability Indicating RP-HPLC Method for Guaifenesin - Sandhya R. Gawai; Kiran Gadge; Sandeep Sonwane (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
For the estimation of Guaifenesin in bulk and formulation, a simple, accurate, and exact stability indicating RP HPLC method was developed and validated. The drug and its breakdown products were separated on a Phenomenex C18 column (250 × 4.6 mm, 5\(μ\)) using a mobile phase of methanol:water (60:40% v/v) under varied forced degradation settings. Eluents were detected at 230 nm and the flow rate was kept constant at 1.0 mL/min. Guaifenesin degraded in acid, alkali, photolytic, and wet heat settings, but remained stable under H2O2 (oxidative) and dry heat conditions in forced degradation trials. Linearity was found in the concentration range of 2-12 g/mL in calibration curve experiments, with regression coefficient (R2) 0.999. The equation obtained was y = 102800 x + 24264. A rapid simple, sensitive and accurate HPLC –UV method has been described for the determination of guaifenesin. From the forced degradation studies it can be concluded that guaifenesin undergoes acid, alkali, wet heat and photolytic degradation.